Inverse Monte Carlo Ray-Tracing method (IMCRT) applied to line-focus reflectors. (February 2016) - Serrano-Aguilera, J.J.; Valenzuela, L.; Fernández-Reche, J.
Highlights: A new numerical method called Inverse Monte Carlo Ray Tracing (IMCRT) is proposed. The method provides line-focus geometries for specific purposes. The PTC reflector geometry can be redefined to achieve better distributed concentrated radiation on the absorber. Continuous line-focus reflector geometries can be proposed for CPV applications on flat absorbers. Abstract: A new method called Inverse Monte Carlo Ray Tracing (IMCRT) is proposed to calculate the numerical description of line-focus concentrator geometries. This paper describes the method application to flat absorbers. The aim of this method is to calculate the reflector geometry so that the resulting concentrated flux profile is as close as possible to some required distribution on the predefined absorber geometry. Parabolic trough collectors (PTC) concentrate radiation onto the absorber inducing thermal gradients around it. The IMCRT method provides the chance to redefine the reflector geometry in order to get homogeneously distributed radiation onto the absorber without secondary reflectors. This method is useful to define continuous linear reflectors for concentrated photovoltaic (CPV) purposes, where a quasi-planar concentrated flux distribution is required onto flat absorbers. The reflector geometries obtained by the IMCRT method for the covered examples have been validated with a 2D in-house ray tracing code.